The Influence of Discontinuities on Rock Mass Quality and Overall Stability of Andesite Rock Slope in West Java (Rudarsko-geološko-naftni zbornik, 2020)
Open-pit mining constitutes a necessary activity for the extraction of rocks and minerals from the Earth. However, open-pit mining activities often result in rock slope stability issues related to the discontinuities of rock masses. Thus, an appropriate cut-slope design in open-pit mining requires good knowledge of the effects of discontinuity on rock mass strength and quality. This study aims to analyze the effect of discontinuity type on rock quality and slope stability. Discontinuity data was collected from the columnar jointed-andesite rock slope in West Java. The analysis showed that the examined andesite slope has a good rock mass quality and very favorable slope stability. However, wedge-type slope failure may occur, which is substantially affected by columnar joints present in the rock mass. Moreover, the analysis indicated that the integral discontinuities present in the andesite outcrops significantly affect the mean values of the discontinuity length, discontinuity spacing, and rock strength. However, the integral discontinuities have little effect on the slope mass rating (SMR). Thus, detailed studies on the contribution of integral discontinuities to the rock mass rating and SMR of different rock types are recommended.